Pengaruh dan Implikasi Sistem Rekrutmen Keagenan Terhadap Kinerja SDM pada AJB Bumiputera 1912 Syariah - Agustya, Riris (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2012)
This study aimed to analyze the influence of the agency recruitment system and its implications for human resources performance on AJB Bumiputera 1912 Sharia. This analysis use descriptive quantitative method with simple regression calculation. The analysis results show that there is a significant influence between agency recruitment systems with human performancein AJB Bumiputera 1912 Syariah Jakarta Regional Office. Implications of the requirements that contained inagency recruitment system were also seen in human performance that is outside the employee's official now.DOI: 10.15408/aiq.v4i2.2549